Crescimento e qualidade óssea de codornas de corte submetidas a diferentes programas de luz - Costa, Heiciane Soares da (2017)
The objective of this study was to evaluate the effects of light programs on growth and bone quality of male and female quail (Coturnix cortunix) raised in equatorial region. A total of 1500 sexually distributed quails were used, distributed in a completely randomized design according to the 2x3 factorial scheme, with two sexes (male and female) and three light programs (natural, intermittent and continuous) with five replicates of 50 birds per treatment. The light programs were applied in the period from 7 to 49 days of age, the natural light program consisting of 12 hours and 30 minutes of natural light and 11 hours and 30 minutes of dark, the intermittent consisting of 18 hours of light and 06 hours of dark, the period of light consisting of 12 hours and 30 minutes of natural light and 5 hours and 30 minutes of artificial light intercalated (1 hour and 06 minutes of light and 1 hour and 06 minutes of dark) and the program Of continuous light consisting of 23 hours of constant light, 12 hours and 30 minutes of natural light and 10 hours and 30 minutes of artificial light and 1 hour of dark. Throughout the experimental period the birds of the different treatments received the same feeding program. To obtain the data for the elaboration of the growth curves we performed weekly slaughterings for bone removal (Shin-bone and Thigh-bone) and subsequent determination of weight and length and dry matter and mineral content. For bone quality, the bones of birds slaughtered at 49 days of age were evaluated. The curves of growth and deposition of dry matter and mineral in the bones were obtained from the non-linear Gompertz model. There was no significant interaction between light and sex programs for estimates of Gompertz curve parameters for all variables studied in the shin-bone and thigh-bone. There was a significant effect of the light program only on the parameter t * of the growth and deposition curve of dry and mineral matter, so that the continuous light program accelerated the time for the maximum growth rate in weight and dry matter deposition And mineral in the bones. Between the sexes, the females presented bones with greater weight and deposition of mineral matter to the maturity, however, they were later, since they presented higher value of t * for these variables. In evaluating the weight, length and diameter of the tibia and femur of the birds at 49 days of age, no interaction between sex and light program was observed, nor was there any significant difference between the light programs. In relation to the effect of sex, it was observed that the females presented greater weight of the thigh-bone. Regarding bone quality, there was a significant influence only of light programs on resistance and bone deformity of the shin-bone, which worsened in birds submitted to the continuous light program. The program of natural and intermittent light should be used in the breeding of quail, as it ensures development and bone quality.